2011
DOI: 10.1525/auk.2011.10262
|View full text |Cite
|
Sign up to set email alerts
|

The Island Syndrome in Coastal Wetland Ecosystems: Convergent Evolution of Large Bills in Mangrove Passerines

Abstract: Resumen.-Las aves paserinas que viven en islas tienden a tener picos más grandes que sus parientes continentales. Los cambios morfológicos podrían estar relacionados con la reducción de la competencia intra e interespecífica. Los gorriones emberízidos que habitan marismas de Norteamérica también presentan picos de tamaños consistentemente mayores. Pusimos a prueba la hipótesis de que los paserinos restringidos a bosques de manglares, otro sistema continental con baja diversidad de especies y con altas densidad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 28 publications
3
24
0
Order By: Relevance
“…The general pattern among passerine birds that inhabit islands versus continental habitats is a trend toward increasing bill size (Scott et al ., ). This pattern was also documented for bird species that inhabit saltmarshes (Greenberg & Olsen, ) and mangrove habitats (Luther & Greenberg, ), habitats that resemble island ecosystems. Greater bill size of island birds may be associated with a shift toward greater generalization in resource use, but specialization in diet (invertebrates) or foraging behaviour (probing in tidal mud) are legitimate alternatives (Greenberg & Olsen, ).…”
Section: Discussionsupporting
confidence: 53%
“…The general pattern among passerine birds that inhabit islands versus continental habitats is a trend toward increasing bill size (Scott et al ., ). This pattern was also documented for bird species that inhabit saltmarshes (Greenberg & Olsen, ) and mangrove habitats (Luther & Greenberg, ), habitats that resemble island ecosystems. Greater bill size of island birds may be associated with a shift toward greater generalization in resource use, but specialization in diet (invertebrates) or foraging behaviour (probing in tidal mud) are legitimate alternatives (Greenberg & Olsen, ).…”
Section: Discussionsupporting
confidence: 53%
“…Previous research indicates that bill size is greater in male YEWA that are year‐round residents in mangrove forests compared with migratory YEWA that inhabit inland terrestrial habitats, even after correcting for body size (Luther and Greenberg ). Based on predictions from recent research on bill morphology of birds restricted to salt marshes (Greenberg and Olsen ; Greenberg et al.…”
Section: Introductionmentioning
confidence: 95%
“…Although the short red mangroves that predominate in Hell's Bay may be structurally similar to the shrubby forest edges occupied elsewhere by this species, the presence of persistent standing water would seem to pose a challenge for a ground-foraging species such as eastern towhee. Additional observations on habitat use and behavior in this population would be of great interest, especially given recent evidence that selective pressures in mangroves may be substantially different than those in adjacent, upland environments (Luther and Greenberg 2011).…”
Section: Eastern Towhee Eastern Towhees Are Relatively Common In a Vmentioning
confidence: 99%
“…Red-bellied woodpecker, downy woodpecker, northern cardinal, common yellowthroat, red-shouldered hawk, Carolina wren, great crested flycatcher, blue jay, eastern towhee, northern flicker, and mourning dove all occurred at greater densities in the pine forests. Luther and Greenberg (2011) suggested that mangroves might function like islands, whereby low species richness would lead to density compensation (e.g., Crowell 1962;MacArthur et al 1972) and niche expansion. We found that the landbird assemblage in Florida's mangroves was species-poor, but we found no evidence of density compensation.…”
Section: Patterns Of Abundance and Challenges In The Enumeration Of Mmentioning
confidence: 99%